Assessing status and trends of open ocean habitats: A regionally resolved approach and Southern Ocean application. (December 2019) - Trebilco, Rowan; Melbourne-Thomas, Jess; Sumner, Michael; Wotherspoon, Simon; Constable, Andrew
Graphical abstract: Highlights: A generalisable framework to assess regional-scale state & change in ocean habitats. Indicators of habitat quality, availability, optimum ranges & thresholds for key taxa. Southern Ocean case study captures novel regional nuance in sea ice habitat change. The Atlantic has the greatest area with SST and Chlorophyll favourable for Krill. Approach enables assessment of open ocean habitats in the Southern Ocean & worldwide. Abstract: Assessing the status and trends of habitats, species, and ecosystems in the vast, remote, and difficult to observe open oceans is a pressing challenge for conserving and managing marine species and ecosystems under a changing climate. Here, we present a framework for assessing the status and trends of key ocean habitat components using synoptic data sources. It aims to quantify ecosystem variability and long-term change, and to provide summaries and indicators of change at scales that are both ecologically meaningful and relevant for management. We illustrate our approach using the Southern Ocean as a case-study and assess habitat based on remotely-sensed sea ice concentration, sea surface temperature (SST) and chlorophyll- a . We use Antarctic krill Euphausia superba as an illustrative example of how thresholds and optimum ranges for key taxa (and the ranges they define) can be used to delimit areas that are likely to constitute "good" habitat. Availability of "good" habitat, in terms of area, provides a simple indicator for quantifying change through time, and for assessing regional differences. Our assessment of sea ice reveals that the absence of a strong trend in the mean annual duration of sea ice cover around Antarctica masks a loss of areas with the longest periods of cover. In the polar latitudinal zone of the East Pacific, the area with the longest ice coverage has declined by 123, 533 km 2 over the past four decades. Our assessment of chlorophyll- a and SST highlights that the area of "good" habitat for krill has increased in the high-latitude zone, but decreased in the polar zone close to the continent in all sectors other than the East Pacific, where the reverse has been true. These examples demonstrate how our general approach can visualise and identify (i) known trends in mean values but also diagnose where changes in the habitat area over time may not match the mean trend; (ii) key habitat thresholds across a range of variables and in different seasons; and (iii) changes in the degree of spatial overlap of areas with desirable ranges for different habitat components. Our approach provides a versatile method to generate summaries of status and trends of ocean habitats at scales meaningful to decision makers. It can readily be adapted to other habitat variables and for other areas, supporting ongoing efforts to assess status and trends of open ocean habitats worldwide.